Complete mitochondrial genome and the phylogenetic position of the pelagic octopus Tremoctopus violaceus (Mollusca: Tremoctopodidae). Issue 2 (3rd July 2018) - Chiu, Yuh-Wen; Chang, Chih-Wei; Shen, Kang-Ning; Ju, Yu-Min; Lin, Hung-Du
Abstract: Tremoctopus violaceus is a small species of pelagic octopods which inhabit in subtropical and tropical open oceans. The mitogenome of T. violaceus is 16, 015 base pairs (bp) in length and contained 13 protein-coding genes, two rRNA genes, and 22 tRNA genes. Sequence analysis showed that the overall base composition is 31.5% for A, 40.47% for T, 7.79% for C, and 20.24% for G. The newly characterized complete mitochondrial genome of T. violaceus will provide essential data for further studies of this endangered species.